Comparison of basic neurocognitive violations in patients with residual schizophrenia with and without history of ischemic stroke - Darii, V. I.; Safonov, D. M.; Дарій, Володимир Іванович; Сафонов, Дмитро Миколайович (My University, 2023)
Relevance. The cognitive symptoms associated with schizophrenia have been a subject of controversy and are often viewed through a dualistic lens. According to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5), these cognitive symptoms can be further elucidated within specific neurocognitive domains. Many of the symptoms of schizophrenia manifest behaviorally and can be challenging to differentiate from the consequences of organic brain impairment, especially when these symptoms involve the frontal and temporal cortex or have a diffuse presentation. Aim – to evaluate neurocognitive deficit in patients with residual schizophrenia with history of ischemic stroke.schizophrenia; ischemic stroke; stroke; neurocognitive domains; neurocognitive functions
Keywords: schizophrenia; ischemic stroke; stroke; neurocognitive domains; neurocognitive functions